2016
DOI: 10.1021/acsinfecdis.6b00109
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Genomic RNA Possesses Conserved G-Quadruplexes Characteristic of the Flaviviridae Family

Abstract: Zika virus has emerged as a global concern because neither a vaccine nor antiviral compounds targeting it exist. A structure for the positive-sense RNA genome has not been established, leading us to look for potential G-quadruplex sequences (PQS) in the genome. The analysis identified >60 PQSs in the Zika genome. To minimize the PQS population, conserved sequences in the Flaviviridae family were found by sequence alignment, identifying seven PQSs in the prM, E, NS1, NS3, and NS5 genes. Next, alignment of 78 Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 37 publications
2
140
0
Order By: Relevance
“…m 6 A) (Lichinchi et al, 2016) in host cells. In addition, computational analyses suggest that the ZIKV genomic RNA possesses conserved G-Quadruplexes (Fleming et al, 2016) as well as the capacity to generate a large number of sfRNAs and sRNAs (Akiyama et al, 2016). Whether any of these mechanisms contribute to ZIKV replication and host cell pathogenesis remains to be functionally determined.…”
Section: Opportunities and Challenges For Zikv Research Using Stem Cellsmentioning
confidence: 99%
“…m 6 A) (Lichinchi et al, 2016) in host cells. In addition, computational analyses suggest that the ZIKV genomic RNA possesses conserved G-Quadruplexes (Fleming et al, 2016) as well as the capacity to generate a large number of sfRNAs and sRNAs (Akiyama et al, 2016). Whether any of these mechanisms contribute to ZIKV replication and host cell pathogenesis remains to be functionally determined.…”
Section: Opportunities and Challenges For Zikv Research Using Stem Cellsmentioning
confidence: 99%
“…Such G4 forming sequences have been reported to be prevalent in genomes, such as immunoglobulin switch regions and promoter regions of oncogenes and telomere ends 4, 5 , as well as in particular RNA domains, such as the first introns, 5′- and 3′- untranslated regions, telomeric RNA 6 , and the genomic RNA of Zika virus replication 7 . Accumulating evidence has suggested that G4s play an intrinsic role in gene expression 814 .…”
Section: Introductionmentioning
confidence: 99%
“…G4s have been reported in the SARS coronavirus7, the human papilloma, hepatitis C, Zika and Ebola virus genomes891011. Among herpesviruses, RNA G4s have been implicated in the regulation of DNA replication and translation of the Epstein–Barr virus1213.…”
mentioning
confidence: 99%